A new combination in the genus Tripidium (Poaceae: Andropogoneae) - Welker, Cassiano A. Dorneles; Vorontsova, Maria S.; Kellogg, Elizabeth A. (Phytotaxa, 2020)
The genus Tripidium Scholz in Valdés & Scholz (2006: 664) (Poaceae: Andropogoneae) currently includes six species, distributed in Asia, southern Europe, and northern Africa, with the greatest diversity in India (Welker et al. 2019). The species of Tripidium have traditionally been treated as part of the “Saccharum complex”, formed by sugarcane [S. officinarum Linnaeus (1753a: 54)] and relatives, being included either in the genus Saccharum Linnaeus (1753a: 54) (e.g., Clayton & Renvoize 1986, Shouliang & Phillips 2006) or in Erianthus Michaux (1803: 54) (e.g., Mukherjee 1958, Besse et al. 1997). However, recent nuclear and plastome phylogenies (Welker et al. 2015, 2019, Lloyd Evans et al. 2019, Welker et al. in press) have unequivocally demonstrated that Tripidium belongs to a different lineage from sugarcane and relatives and thus should be accepted as a genus distinct from Saccharum or Erianthus. According to the plastome phylogeny of Welker et al. (in press), Tripidium is sister to the newly circumscribed subtribe Rottboelliinae, which comprises the genera Rottboellia Naezén (1779: 23) s.str. and Coix Linnaeus (1753b: 972).